A nonlocal parabolic system with application to a thermoelastic problem - Y. Lin; R. J. Tait (International Journal of Mathematics and Mathematical Sciences, 1999)
A system modeling the thermoelastic bards contacts is studied. The problem is first transformed into an equivalent nonlocal parabolic systems using a transformation, and then the existence and uniqueness of the solutions are demonstrated via the theoretical potential representation theory of the parabolic equations. Finally some realistic situations in the applications are discussed using the results obtained in this paper.